Sexual Minority Status and Psychological Risk for Suicide Attempt: A Serial Multiple Mediation Model of Social Support and Emotion Regulation - Chang, Cindy J.; Fehling, Kara Binder; Selby, Edward A. (Frontiers in Psychiatry, 2020)
The current study examined the relation between sexual minority status, social support, emotion dysregulation, and suicide attempt in a community sample. A total of 388 community and college adults completed a one-time survey examining self-injury and suicidality. Findings demonstrated that that social support and emotion regulation, independently and in sequence, mediated the relation between sexual minority status and suicide attempt. The reverse mediation model with emotion regulation as the first mediator and social support as the second mediator was also significant. Social support and emotion regulation may both be related and may explain the relation between sexual minority status and suicide attempt. If replicated longitudinally, these findings shed light on specific risk factors and their interrelations, which may have important implications for preventing suicide in sexual minorities.